Genetic screening reveals high frequency of PARK2 mutations and reduced Parkin expression conferring risk for Parkinsonism in North West India. Issue 2 (3rd September 2009) - Vinish, Monika; Prabhakar, Sudesh; Khullar, Madhu; Verma, Indu; Anand, Akshay
Abstract : Background: Among several aetiological factors, PARK2 mutations are the most common cause of Parkinson disease (PD) that result in degeneration of dopaminergic neurons in the substantia nigra. Methods: In order to examine the contribution of PARK2 mutations and corresponding Parkin expression in blood of North West Indian PD patients, the authors screened 120 000 patients from 2001 to 2006 for features of PD using UK Parkinson disease society brain bank clinical diagnostic criteria (UKPDBBC), and tested PARK2 mutations in 69 of those that fulfilled this criteria. 43 controls lacking extrapyramidal signs were also analysed. Results: The PCR analysis revealed the occurrence of homozygous deletions in 28 of 69 samples analysed (40.5%) represented by exon-1 (15.9%), exon-3 (11.5%), and exon-12 (11.5%). Sequencing revealed point mutations in exon 4 and exon 9 in six of these patients (8.7%) including one novel missense Gly1083Trp mutation in one patient. Parkin estimation was done by combination of immunolocalisation and FACS analysis revealing reduced Parkin expression among PD patients. The mutations in exons 1, 3 and 12 among sporadic PD patients were found to be higher among younger onset variants (age<45 years). This report also constitutes the first evidence that PARK 2 mutations contribute to the aberration in Parkin expression in blood leading to PD.